Gut microbiota composition before infection determines the Salmonella super- and low-shedder phenotypes in chicken - Kempf, Florent; Menanteau, Pierrette; Rychlik, Ivan; Kubasová, Tereza; Trotereau, Jérôme; Virlogeux-Payant, Isabelle; Schaeffer, Samantha; Schouler, Catherine; Drumo, Rosanna; Guitton, Edouard; Velge, Philippe (Microbial biotechnology, 2020)
Heterogeneity of infection and extreme shedding patterns are common features of animal infectious diseases. Individual hosts that are super-shedders are key targets for control strategies. Nevertheless, the mechanisms associated with the emergence of super-shedders remain largely unknown. During chicken salmonellosis, a high heterogeneity of infection is observed when animal-to-animal cross-contaminations and reinfections are reduced. We hypothesized that unlike super-shedders, low-shedders would be able to block the first Salmonella colonization thanks to a different gut microbiota. The present study demonstrates that (i) axenic and antibiotic-treated chicks are more prone to become super-shedders; (ii) super or low-shedder phenotypes can be acquired through microbiota transfer; (iii) specific gut microbiota taxonomic features determine whether the chicks develop a low- and super-shedder phenotype after Salmonella infection in isolator; (iv) partial protection can be conferred by inoculation of four commensal bacteria prior to Salmonella infection. This study demonstrates the key role plays by gut microbiota composition in the heterogeneity of infection and pave the way for developing predictive biomarkers and protective probiotics.
Keywords: vylučování bakterií z těla; Gastrointestinal Microbiome; kur domácí; Chickens; Phenotype; Bacterial Shedding; Escherichia coli O157; Salmonella; fenotyp; Animals; zvířata; střevní mikroflóra